DIGITAL TRANSFORMATION IN FAMILY CARD (KK) SERVICES THROUGH THE DIGITAL POPULATION IDENTITY (IKD) APPLICATION - Nur Adinda Ramadhani; Isna Fitria Agustina (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study aims to analyze how the digital transformation of Family Card (KK) renewal services through the Digital Population Identity (IKD) application at the Sidoarjo Regency Population and Civil Registration Office is progressing, specifically in terms of technological readiness, human resource competencies, policy support, and community participation in utilizing digital services. Method: This study employs a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. Informants were selected using purposive sampling, involving Disdukcapil officials and members of the public who use the IKD. Data analysis was conducted using the Miles and Huberman model, referencing Vial’s (2019) digital transformation framework. Results: The findings indicate that the IKD service has successfully made the process of splitting family cards more practical, faster, and accessible from home. Infrastructure and human resources are sufficiently supportive, though minor challenges remain, such as limited devices, network disruptions, and an activation process that initially confused some members of the public. Service procedures have become more efficient compared to manual methods, although they still depend on system stability. Public participation has also increased, although it still requires stronger guidance and digital literacy. Novelty: The novelty of this research lies in its specific focus on IKD-based family registration services, using a comprehensive approach that integrates technological, human resource, organizational, and community aspects within a single framework of digital transformation, thereby providing new insights into the development of more adaptive and relevant digital public services.